Unique presentation of rectal prolapse as alarm symptom for pediatric abdominal compartment syndrome - Maria E. Tecos; Matthew Ballweg; Angela Hanna; Patrick Thomas; Abdalla Zarroug (Elsevier, 2022)
Rectal prolapse is typically associated with chronic constipation in the pediatric population. Historically, it has been well managed with the adoption of an aggressive bowel regimen, with refractory cases responding well to operative intervention. Here, we present a case of new, acute onset refractory rectal prolapse as an alarm symptom of abdominal compartment syndrome in a 2-year-old female. To our knowledge, this presentation of rectal prolapse heralding abdominal compartment syndrome is unique in the available pediatric literature.